Analisis Efektivitas Biaya Laparoskopik Herniotomy dan Open Herniotomy pada Pasien Hernia Inguinalis Unilateral di Rumah Sakit Gading Pluit Jakarta Utara Tahun 2014 - Tjitra, Dewi Saputra (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
This thesis is an economic evaluation with a cross sectional quantitative method design, observational and using comparative studies between two herniotomy techniques. The aim of this thesis is to analyze the cost effectiveness between patients with Laparoscopic Herniotomy and patients with Open Herniotomy of the inguinal hernia. This research is using Activity Based Costing with simple distribution to achieve total cost and then compared with the output, therefore cost effectiveness ratio (CER) is achieved. The CER is then compared to understand which is the lesser cost therefore is more effective. The research result shows that Open Herniotomy gives a smaller CER than the Laparoscopic Herniotomy. Therefore it is found that Open Herniotomy is more effective compared with Laparoscopic Herniotomy.